Peculiarities of Organization of Students’ Online Educational Internship - Maria Sazanova; Marina Morozova (ARPHA Proceedings, 2022)
The paper sets out to present the experience of organizing students’ online educational internship. The educational internship for the bachelors of Education, majoring in Health and Safety & Physical Education, is introductory, the first one in the curriculum. The distance educational internship was organized on the MS Teams digital platform using team work. The students’ online activities involved analyzing scientific, popular science, methodological and official information on health and safety and physical education, as well as on the disciplines that provide the meta-subject approach and inter-subject communications when teaching these subjects at school. The key methods were the project method and the case method. The students were given different cases, such as to analyze the content of video clips and websites, to develop environmental excursions and algorithms for modeling the volcano, to determine the optimal physical recreation and its components for people of different ages. The main advantages of students’ distance educational internship are a larger number of tasks completed by students compared to the full-time format, the use of different methods and technologies to organize students’ team work. The main problems concerning the distance educational internship include teachers significantly overloaded with the task development and evaluation, the long hours students spend working at the computer and technical issues. It is important to find a reasonable compromise between the amount of the proposed work with the information, the optimal time and safe operation in an electronic environment when organizing internships in an online format.